Cyberbullying on Social Media: Causes, Effects, Prevention and Treatment - Yusuf, Nur Mawakhira; Ahsan, Amrul Aysar; Sarli, Rinda; Ambarwati, Annisa Dewi Ayu Tri (Universitas Muhammadiyah Metro, 2026)
This research discusses the phenomenon of cyberbullying on social media which has a significant impact on individual mental health. Cyberbullying is a form of bullying carried out through social media that occurs in the form of sending negative comments, aggressive messages, or spreading negative content on various social media platforms. This research uses a qualitative method with a phenomenological approach. The interview method was conducted on 6 subjects with an age range of 20-25 years. The purpose of this study is to analyse cyberbullying behaviour on social media, causal factors, impacts, prevention and handling of cyberbullying behaviour on social media. The results of this study indicate that cyberbullying behaviour on social media requires full self-awareness from each user and support from the surrounding environment. Positive thinking is a step and strategy that can help social media users to maintain emotional balance and reduce the adverse effects of cyberbullying behaviour on social media.